Linking natural capital, benefits and beneficiaries: The role of participatory mapping and logic chains for community engagement. Issue 134 (August 2022) - Burdon, D.; Potts, T.; Barnard, S.; Boyes, S.J.; Lannin, A.
Abstract: There has been increasing attention within environmental science, policy and management on the application of natural capital approaches. Despite this, there is an evidence gap in terms of our current understanding of how natural capital and societal benefits are identified at the local scale. This paper presents a novel stakeholder-driven approach to participatory mapping which enables engagement of communities in natural capital discussions across a series of face-to-face workshops. A real-world application is presented for the Deben Estuary, Suffolk (UK); however, the methodological framework could be applied to any global ecosystem (terrestrial, freshwater, estuarine, marine, urban) and community setting. All outputs developed and produced by the Deben Estuary stakeholders, who represent 26 different organisations, were used in subsequent workshops to support scenarios assessments and logic chain developments. The development of logic chains allow for the relationships between natural capital, benefits and beneficiaries to be viewed through multiple lenses, recognising the importance of natural capital in delivering societal benefits and the reliance of beneficiaries on those benefits and the natural capital which underpins them. From a management perspective, the results of this study help to identify which benefits, and therefore which beneficiaries, may be impacted by an intervention, and what direction that impact may take. Graphical Abstract: ga1 Highlights: There is increasing attention in science and policy on natural capital approaches. Evidence gap of how natural capital and benefits are identified at the local scale. Participatory mapping is advocated to support local natural capital discussions. Logic chains enable relationships to be viewed through multiple lenses. The 10-step stakeholder-driven framework has global relevance across all ecosystems.